Evolutionary map of the Universe (EMU): 18-cm OH-maser discovery in ASKAP continuum images of the SCORPIO field. Issue 1 (22nd February 2022) - Ingallinera, A; Cavallaro, F; Loru, S; Marvil, J; Umana, G; Trigilio, C; Breen, S; Bordiu, C; Buemi, C S; Bufano, F; Collier, J; Etoka, S; et al.
ABSTRACT: Low- and intermediate-mass stars end their life dispersing their outer layers into the circumstellar medium, during the asymptotic and post-asymptotic giant branch phases. OH masers at 18 cm offer an effective way to probe their circumstellar environment. In this work, we present the discovery of seven OH maser sources likely associated with such evolved stars from the visual inspection of Australian SKA Pathfinder (ASKAP) continuum images. These seven sources do not emit real continuum emission, but the high sensitivity of our images allows us to detect their maser emission, resembling continuum sources. To confirm their nature, we carried out spectral-line observations with ATCA. All the sources showed the double-peaked spectra at 1612 MHz, typical of evolved stars. The detection of maser emission in continuum images can be a complementary and easy-to-use method to discover new maser sources with the large-area deep surveys conducted with the Square Kilometre Array (SKA) precursors. The implication for radio stars studies are remarkable since pure OH maser sources (i.e. with no continuum associated) represent, at a sensitivity of 100 μ Jy beam^-1, about 4 per cent of all Galactic sources and by far the most numerous stellar population.